Simple Additive Weighting (SAW) Method for Admission of New Students Entitled to Scholarships at STMIK Logika Medan - Muhammad Ihsan; Kesadaran Luaha (UIN Sumatera Utara, 2022)
New student admissions will certainly be done annually by the university. However, in the process, universities sometimes collaborate in the selection of campus scholars. Based on this, this research was conducted to develop a system for selecting new students who are entitled to receive scholarships at STMIK Logika Medan. The results of this study indicate that: :(a) Having a decision support system using the SAW method can help facilitate campus tasks in determining potential new students to accept; (b) To identify potential new students, they must meet the criteria that have been established; (c) Based on the data test results of 5 prospective new students, it was found that the prospective new student named Syifa Annisa had the highest score. Based on the results of these tests, the built application is able to provide information about the eligibility decision to admit new students;(d)Reporting in the form of sorting the final system results from highest to lowest value can make the resulting population value data easier to read for related parties.